Empowering teacher education with jigsaw techniques: insights from language learners’ listening tasks - Banaruee, Hassan; Farsani, Danyal; Khatin-Zadeh, Omid (Frontiers in Education, 2025)
Developing a sustainable education requires consideration of social and psychological factors in the classroom. One such implementation is the jigsaw technique, a cooperative approach that is less frequently investigated. This study aimed to examine the effectiveness of jigsaw listening techniques in teaching advanced learners of English as a Foreign Language (EFL). Participants were divided into two groups: jigsaw group or diagnostic group. To achieve the objectives of the study, English listening tasks were administered to the participants once as both pre-tests and post-tests. Descriptive statistics from the pre-test results were used to evaluate the level of their homogeneity. Two series of paired samples t-tests were conducted using Statistical Package for the Social Sciences (SPSS) to investigate changes from pre-test to post-test after the intervention. The results indicated that both listening techniques were effective, but jigsaw techniques led to higher listening proficiency. By the end of the course, learners in the jigsaw group were more homogeneous. The findings suggest that high levels of social interactions among students contribute to improved instructional processes and play a crucial role in learning gains when using jigsaw techniques. Social skills, which are essential prerequisites for successful cooperation, require explicit teaching and development and can be promoted with jigsaw techniques in the classroom. This study introduced and developed seven jigsaw techniques that are significantly complementary to EFL classes.